School-Based Sexual Health and Reproduction Education in Early Adolescents at Muhammadiyah Junior High School - Hastuti, Lidia; Wahyuni, Tri; Mardiyani, Ridha; Rahmawati, Annisa (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Background: Switch on. Adolescence is also a critical period that must be properly addressed and addressed by adolescents. Changes in body shape, especially in the reproductive organs, invite many questions from adolescents, such as the presence of bleeding from the vagina for the first time (menarche), the first wet dream in boys (semenarche). Teenagers must be prepared to face puberty with various changes and the first experiences that occur. Teenagers need information that can solve the problems they face. Health education about sexual and reproductive health is very important to do, as an effort to increase knowledge in dealing with puberty. The sexual and reproductive health education program for adolescents in facing puberty is one solution that can be done to increase students' knowledge in facing puberty. This activity aims to increase adolescents' knowledge about puberty and maintenance of the reproductive organs as well as to form positive attitudes and behaviors in adolescents. Method: Providing health education to 120 grade 7 students in stages using podcast media, distributing leaflets and posters. Evaluate activities by measuring pre-test and post-test scores. Results: There was a significant difference in knowledge from before and after the program was implemented with a value of p = 0.000 (p <0.01) with a mean pretest score of 3.43 ± SD 2.36 and a mean posttest score of 7.26 ± SD 1.79. The mean difference is 3.83±SD 2.57. Conclusion: Sexual and reproductive health education is proven to increase students' knowledge in dealing with puberty and care for reproductive organs.